Screening Novel Vaccine Candidates for Leishmania Donovani by Combining Differential Proteomics and Immunoinformatics Analysis - Zhang, Jianhui; Li, Jiao; Hu, Kaifeng; Zhou, Qi; Chen, Xiaoxiao; He, Jinlei; Yin, Shuangshuang; Chi, Yangjian; Liao, Xuechun; Xiao, Yuying; Qin, Hanxiao; Zheng, Zhiwan; et al. (Frontiers in Immunology, 2022)
Visceral leishmaniasis (VL), also known as kala-azar, is the most dangerous form of leishmaniasis. Currently no effective vaccine is available for clinical use. Since the pathogenicity of different Leishmania strains is inconsistent, the differentially expressed proteins in Leishmania strains may play an important role as virulence factors in pathogenesis. Therefore, effective vaccine candidate targets may exist in the differentially expressed proteins. In this study, we used differential proteomics analysis to find the differentially expressed proteins in two Leishmania donovani strains, and combined with immunoinformatics analysis to find new vaccine candidates. The differentially expressed proteins from L. DD8 (low virulent) and L. 9044 (virulent) strains were analyzed by LC-MS/MS, and preliminarily screened by antigenicity, allergenicity and homology evaluation. The binding peptides of MHC Ⅱ, IFN-γ and MHC Ⅰ from differentially expressed proteins were then predicted and calculated for the second screening. IFN-γ/IL-10 ratios and conserved domain prediction were performed to choose more desirable differentially expressed proteins. Finally, the 3D structures of three vaccine candidate proteins were produced and submitted for molecular dynamics simulation and molecular docking interaction with TLR4/MD2. The results showed that 396 differentially expressed proteins were identified by LC-MS/MS, and 155 differentially expressed proteins were selected through antigenicity, allergenicity and homology evaluation. Finally, 16 proteins whose percentages of MHC Ⅱ, IFN-γ and MHC Ⅰ binding peptides were greater than those of control groups (TSA, LmSTI1, LeIF, Leish-111f) were considered to be suitable vaccine candidates. Among the 16 candidates, amino acid permease, amastin-like protein and the hypothetical protein (XP_003865405.1) simultaneously had the large ratios of IFN-γ/IL-10 and high percentages of MHC Ⅱ, IFN-γ and MHC Ⅰ, which should be focused on. In conclusion, our comprehensive work provided a methodological basis to screen new vaccine candidates for a better intervention against VL and associated diseases